(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Non-adherence to anti-tuberculous treatment can extend the duration of illness, contribute to loss to follow-up and reduce treatment success in children, but determinants of adherence in children are not fully understood. Methods: A prospective observational study of 184 children with drug-susceptible TB (DSTB) who were receiving treatment in a tertiary care center was conducted and adherence, treatment outcomes, and modifiable risk factors were assessed. Results: At least 90% of prescribed doses without a prolonged gap in treatment was documented in 141 (76.6%) children and in 43 (23.4%) children, poor adherence was documented, with overall treatment success of 88.0%, but lower among poorly adherent children, compared to those with good adherence (69.8% vs 93.6%, p<0.001). Poor adherence was associated with loss to follow-up (18.6% vs 2.1%, p<0.001), longer treatment duration (7.1±1.5 vs 6.4±0.9 months, p<0.001), adolescent age (adjusted odds ratio 2.64, 95% confidence interval 1.28-5.43), travel time exceeding 60 minutes (2.39, 1.18-4.87), low caregiver education (2.27, 1.10-4.69), adverse drug effects (3.09, 1.42-6.72), and missed counseling sessions (3.46, 1.52-7.87). Conclusion: Pediatric TB programs should integrate early identification of adherence risk, adherence counseling for caregivers, managing adverse effects, and decentralized adherence support into adolescent TB programs to increase treatment completion and treatment success.